Penentuan Jenis Bahan Aktif Insektisida Dalam Pengendalian Spodoptera exigua Menggunakan Bioassay Tanpa Rearing - Catur Raharjo Febrayanto; Fitri Susiyanti; Koko Dwi Sutanto; Arina Maulinda; Adiba Eva Perdani; Didi Carsidi; Bagus Nur Rochman; Fahri Ali; Muhammad Bachtiar Musthafa (Jurnal Penelitian Pertanian Terapan, 2025)
Spodoptera exigua is one of the major pests of shallot plants that is difficult to control by farmers in brebes regency. Control of S. Exigua generally uses chemical insecticides. This study aims to test the efficacy of insecticides against S. Exigua larvae using the bioassay without rearing method, determine the efficacy of insecticides on S. Exigua larvae, and insecticides which is recommended to control S. Exigua larvae. This research uses a quantitative paradigm with an experimental design. The types of insecticides used consist of 7 commercial brands containing different active ingredients and one control tested on S. Exigua larvae from Kedunguter village, Brebes subdistrict, Brebes regency. Data analysis was performed using univariate analysis, followed by Duncan's Multiple Range Test and hierarchical cluster test. The results showed that the bioassay without rearing method can be used to determine the type of insecticide to be used for controlling S. exigua. Mortality of S. exigua larvae varied against insecticides. The lowest mortality occurred in brand A, brand C, and brand B, while the highest mortality occurred in brand F and brand E. There is a tendency of cross-resistance occurrence in S. exigua between the active ingredients abamectin, emamectin benzoate, and beta-cyfluthrin. Insecticides which recommended to control S. exigua larvae are brand F and brand E.